Impact of interorganelle coordination between the conventional early secretory pathway and autophagy in cellular homeostasis and stress response - Tapia, Diego; Cavieres, Viviana A.; Burgos, Patricia V.; Cancino, Jorge (Frontiers in Cell and Developmental Biology, 2023)
The secretory and autophagy pathways are two essential interconnected pathways crucial for cellular homeostasis maintenance. The secretory route is an anabolic cellular process responsible for the synthesis and delivery of proteins destined to different locations including different organelles, the extracellular media, and the plasma membrane. On the other hand, autophagy is a catabolic cellular process that delivers cytoplasmic components, including organelles, to the lysosome in double-membrane vesicles called autophagosomes. Interestingly, the biogenesis of autophagosomes is driven by a variety of cytosolic conserved protein machineries that are recruited to key organelles of the secretory pathway, including the endoplasmic reticulum and Golgi apparatus and the interphase between these two membrane platforms. However, the extent of this functional inter organelle coordination including its regulatory principles, molecular architecture and inter organelle cooperation are still poorly understood. Here, we summarized the most relevant evidence about those common molecular players involved in these interconnected pathways, and the mechanisms implicated in their coordination, cooperation, and functional engagement necessary to keep homeostasis in mammalian cells, highlighting the findings that support the inter organelle crosstalk between the ER-Golgi interphase and autophagy pathways under normal and stressful scenarios.